2003
DOI: 10.1021/ol0269704
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of the Putative Structure of (−)-Oryzoxymycin

Abstract: [reaction: see text] A short asymmetric synthesis of (2'S,5R,6R)-2'-[6-amino-5-hydroxy-1,3-cyclohexadiene-1-carbonyloxy]propionic acid, the enantiomer of the reported structure of (+)-oryzoxymycin is described. The reported spectral data does not match that obtained for synthetic "oryzoxymycin".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…The complementary of 5 and 9 was emphasized by the synthesis of both enantiomers of the natural product valienone (19) starting from these compounds (Scheme 3). [16] 1,2-Amino alcohols are prevalent in natural products and pharmaceuticals, for example in adrenaline and beta blockers.…”
Section: Dedicated To Professor Heinz G Flossmentioning
confidence: 99%
See 1 more Smart Citation
“…The complementary of 5 and 9 was emphasized by the synthesis of both enantiomers of the natural product valienone (19) starting from these compounds (Scheme 3). [16] 1,2-Amino alcohols are prevalent in natural products and pharmaceuticals, for example in adrenaline and beta blockers.…”
Section: Dedicated To Professor Heinz G Flossmentioning
confidence: 99%
“…The relative configuration of 3 was verified by single-crystal X-ray structure analysis of the corresponding bisacetyl-protected methylester 20 (see the Supporting Information). Steel et al [19] recently reported that 3, synthesized in racemic form, can be oxidized stereoselectively analogous to the oxidation of the diols 5 and 9. Furthermore, 3 and derivatives thereof have been used in cycloaddition reactions.…”
Section: Dedicated To Professor Heinz G Flossmentioning
confidence: 99%
“…While the two amino acids 2,3-trans-CHA (2) and 3,4-trans-CHA (4) proved to be just as good as the L-proline catalyst with respect to enantioselectivity, they intrinsically possess several advantages. As we and others have shown for 2 and 4, and for the respective diols 2,3-trans-CHD (3) and 3,4-trans-CHD (5), 39,41,48,49 the carboxylate moiety and the vicinal diol or amino alcohol moieties can be protected selectively. The 1,3-diene system of these compounds can be modified highly specifically through oxidative or reductive processes (e.g., epoxidation, dihydroxylation, selective hydrogenation), as well as via pericyclic reactions such as Diels-Alder and hetero-Diels-Alder additions (Scheme 5).…”
Section: Methodsmentioning
confidence: 52%
“…1 They act as electron deficient alkenes and react with different dienes to yield cyclic constrained b-amino acids after reduction of the nitro group. [2][3][4][5] Concerning asymmetric Diels-Alder syntheses, it is surprising that only a few methods involving the use of a chiral b-nitroacrylate have been reported so far. 6,7 Indeed, chiral cyclic b-amino acids are an important class of compounds as they are constituents of natural products such as alkaloids, peptides, and b-lactam antibiotics.…”
Section: Introductionmentioning
confidence: 99%